Portable particle mass spectrometer. Issue 12 (25th April 2022) - Hsiao, Chun-Jen; Özdemir, Abdil; Lin, Jung-Lee; Chen, Chung-Hsuan
Abstract : In situ and real-time analysis of airborne particulate matter mass distributions using portable particle mass spectrometer. Abstract : Particle pollutants in air have been confirmed to damage human health. The PM10 concentration is an important parameter for air quality determination. In this study, a portable quadrupole ion trap mass spectrometer (QIT-MS) was developed and used to quantitate microparticles and particulate standards. The instrument can be used to perform online analysis of various microsized particles. The instrument can be used to analyze various sizes of disperse particles with accurate mass by a histogram profile. The overall detection efficiencies of particles in the sample for polystyrene were obtained. PM10-like reference materials were used for calibration to analyze the size and mass distribution of an environmental sample. The instrument shows the potential for quantitation of different particles of an unknown sample.